Assessment of Aflatoxin Levels in Indigenous Chicken Tissues and Eggs in Western Kenya - Tarus, J. K.; Rachuonyo, H. A.; Omega, J. A.; Ochuodho, J. O. (African Journal of Education,Science and Technology (AJEST), 2019)
Aflatoxin contamination of chicken products can significantly impact food safety due to presence of residues in the products. A study was conducted to investigate presence of aflatoxins in meat and eggs of indigenous chicken in Busia, Kakamega and Siaya Counties of Western Kenya. Insert study objective at this point before methodology. Purposive selection of farmers was carried out based on indigenous chicken population (above 10 chicken per farmer), production systems and activeness of farmer groups. A multi-stage sampling was used involving: Counties sub Counties, Divisions/Wards, Locations and Farmer groups. From each group, five members completed a questionnaire. A total of 180 farmers were interviewed on aspects such as production systems and mycotoxin awareness. An adult (>36 weeks old) and a young (12 - 16 weeks old) chicken was obtained from each identified farmer and slaughtered. Approximately 30g of the thigh and breast muscles, liver and kidney were obtained from each chicken together with two eggs collected, from farmer 1 and 5 of each group and tested for presence of aflatoxin. Samples were tested for aflatoxin by Enzyme-linked Immunosorbent Assay (ELISA). Tissues and eggs from chicken reared under free range system had higher aflatoxin means in parts per billion (ppb) (Breast muscle, 3.143; Kidney, 2.157; Liver; 4.619; Thigh muscle, 3.371; Eggs, 0.078) than those reared in semi free range (Breast muscle, 3.753; Kidney, 1.926; Liver; 3.953; Thigh muscle, 2.276; Eggs, 0.066) The difference in levels of aflatoxin between tissues and eggs was significant at p< 0.05. However, aflatoxin levels in tissues were lower than the KEBS, WHO/FAO safety levels of 10 and 20 ppb, respectively. This study confirms the presence of aflatoxins in chicken tissues and eggs. There is need for preventive measures to be instituted to mitigate this challenge and farmers made aware of the effects of aflatoxicosis in poultry and poultry products.